PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA GURU ( STUDY PADA PERGURUAN MUHAMMDIYAH SETIABUDI PAMULANG ) - ASRIDAH WARNI TANJUNG (Universitas Pamulang, 2018)
Influence Leadership Principal Work Motivation and Work Discipline on Teacher Performance (Study At Perguruam Muhammadiyah Setiabudi Pamulang). Supervisor I Dr. H. Amin K. Elfachmi. S.Pd, SE, MM. Second Advisor Dr. Ir. Umi Rusilowati, MM. Examiner I Dr. H. Dayat Hidayat, M.M. Examiner II Dr. H. Hidayat Bin Kaiman, M.M. This research is a quantitative descriptive research. Population taken is all teachers of college muhammadiyah setiabudi pamulang, which amounted to 100 respondents. This instrument is a questionnaire. Data analysis using descriptive data analysis presented in percentage. the analysis used is the validity test, reliability test and path analysis. The results showed that (1) There is a Leadership Influence on Performance. This can be seen from the results of the table coefficient by using SPSS version 22 analysis, then the value of titung for Leadership variable (X1) is 22,619, while the value of ttable for n = 100 is 1.66055. So because tcount> ttable, 22,619> 1.66055 then 〖h〗 _0 rejected and 〖h〗 _a1 accepted so it can be concluded that Leadership variable (X1) has a positive influence on Performance. (2) There is Influence of Motivation to Performance. It can be seen from the result of coefficient table by using SPSS Version 22 calculation analysis, thitung for Motivation variable (X2) is 1.034, while ttable for n = 100 is 1.66055. So because the value of t count <ttabel, that is 1.801 <1.66055 then H2 accepted and concluded that Motivation (X2) has a positive influence on Performance. (3) There is No Effect between Discipline on Performance. It can be seen from the result of coefficient table by using SPSS Version 22 calculation analysis, thitung for Discipline variable (X3) is 11,988, while ttable for n = 100 is 1.66055. So because tcount <ttable, ie -0.2243 <1.66055 then H3 is rejected and it can be concluded that Discipline (X3) has no effect on Performance (Y). (4) There is Influence between Leadership, Motivation and Discipline on Performance. This can be seen from ANOVA result using SPSS version 22 calculation analysis, shows the value of Fhitung for the three independent variables, namely Leadership (X1), Motivation (X2) and Discipline (X3) is obtained Fcount of 592,198, while Ftable for n = 100 is of 2.70. So the value Fcount> Ftable l, ie 592,198> 2.70 so that H3 accepted and can be concluded that between Leadership (X1), Motivation (X2), and Discipline (X3) simultaneously affect Performance.Key words: Principal Leadership, Work Motivation, Work Discipline and Teacher Performance